2016
DOI: 10.1161/atvbaha.115.306931
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage IKKα Deficiency Suppresses Akt Phosphorylation, Reduces Cell Survival, and Decreases Early Atherosclerosis

Abstract: Objective The IκB kinase (IKK) is an enzyme complex that initiates the NF-κB transcription factor cascade, which is important in regulating multiple cellular responses. IKK alpha (IKKα) is directly associated with two major pro-survival pathways, PI3K/Akt and NF-κB, but its role in cell survival is not clear. Macrophages play critical roles in the pathogenesis of atherosclerosis, yet the impact of IKKα signaling on macrophage survival and atherogenesis remains unclear. Approach and Results Here we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Mechanistically, PKB mediates macrophage survival by cross-talking with NF-κB, p38 MAPK and antiapoptotic signals mediated by Mcl1 and Bcl-xL [98][99][100]. Notably, IKK deficiency in macrophages results in decreased viability accompanied with reduced activation of PKB [101], indicating a potential feedback between PKB-IKK/NF-κB in the regulation of macrophage survival.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…Mechanistically, PKB mediates macrophage survival by cross-talking with NF-κB, p38 MAPK and antiapoptotic signals mediated by Mcl1 and Bcl-xL [98][99][100]. Notably, IKK deficiency in macrophages results in decreased viability accompanied with reduced activation of PKB [101], indicating a potential feedback between PKB-IKK/NF-κB in the regulation of macrophage survival.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…Interestingly, both genetic deficiency of IKK α and pharmacological inhibition of IKK α suppressed Akt phosphorylation in macrophages. 56 Transplantation studies revealed that loss of IKK α in the hematopoietic cells of Ldlr −/− mice was associated with reduced atherosclerotic lesion size, and the lesions displayed increased numbers of apoptotic macrophages compared with control mice transplanted with WT cells. 56 Tilstam et al have reported that knock-in of a non-activatable IKK α kinase (Ikk α AA/AA) mutant in the bone marrow of Apoe −/− mice influenced hematopoiesis but not atherosclerosis.…”
Section: Role Of the Upr Signaling Pathway In Er Stress In Macrophagesmentioning
confidence: 99%
“…56 Transplantation studies revealed that loss of IKK α in the hematopoietic cells of Ldlr −/− mice was associated with reduced atherosclerotic lesion size, and the lesions displayed increased numbers of apoptotic macrophages compared with control mice transplanted with WT cells. 56 Tilstam et al have reported that knock-in of a non-activatable IKK α kinase (Ikk α AA/AA) mutant in the bone marrow of Apoe −/− mice influenced hematopoiesis but not atherosclerosis. 57 However, it is important to note that IKK α activity was not abolished in these Ikk α AA/AA mice, 57 as evidenced by a lack of morphogenic defects and downstream signaling effects specific to loss of IKK α in the original descriptions.…”
Section: Role Of the Upr Signaling Pathway In Er Stress In Macrophagesmentioning
confidence: 99%
“…The same group reported that inhibition of IKKα (involved in alternative NF-κB activation) or its deletion in macrophages limits cell survival, presumably through suppression of mTORC2-mediated AKT S473 phosphorylation, while enhancing macrophage inflammatory status. Moreover, deletion of IKKα in bone marrowderived cells reduces early atherosclerosis in Ldlr −/− mice, 64 further supporting a role for macrophage apoptosis in limiting the development of early lesions. However, IKKα deletion profoundly affects T-and B-cell development and functions, which may also account for the atheroprotective effect.…”
Section: Innate Immune Functionsmentioning
confidence: 76%